Wetland Science 2017
DOI: 10.1007/978-81-322-3715-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Coastal Wetlands: An Appraisal of the Policy and Legal Framework in South Asian Nations

Abstract: Coastal wetlands are highly productive ecosystems that provide wide range of ecosystem services. South Asia, with its long coastline, has diverse coastal wetland ecosystems that are subject to serious threats caused by pollution and overexploitation of resources. The legal environmental instruments of different nations illustrate their intent towards the sustainable environmental governance. South Asian nations have formulated policies and legal framework for efficient management of coastal wetland resources a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, in recent years, because of climate variability and climate extremes, management plans are progressively proactive and considerate of longer duration into the future, while devising appropriate adaptation responses for coping. This is evident from the shoreline management plans of the UK, Netherlands, etc., which look at the timescale of 100 years [29][30][31].…”
Section: Framework For Development Of Integrated Coastal Zone Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, because of climate variability and climate extremes, management plans are progressively proactive and considerate of longer duration into the future, while devising appropriate adaptation responses for coping. This is evident from the shoreline management plans of the UK, Netherlands, etc., which look at the timescale of 100 years [29][30][31].…”
Section: Framework For Development Of Integrated Coastal Zone Managementmentioning
confidence: 99%
“…Coastal erosion has three potential adaptation strategies, i.e., protect, accommodate, and retreat as per the IPCC Coastal management strategy, and it very well fits into the Integrated Coastal Zone Management Plan (ICZMP) of the Government of Kerala [28][29][30][31]. The study revealed that areas in these Kavvayi wetlands are vulnerable zones and, hence, priority needs to be given to those areas, as these have a large number of economic activities and are related to their livelihoods too.…”
Section: Framework For Development Of Integrated Coastal Zone Managementmentioning
confidence: 99%
“…tuna), mangroves and the organisms that reside within them are also connected by sea and could fall under this remit. Due to these connections, UNCLOS can be used as a framework for regional cooperation on conservation (Ramesh et al 2017). Articles that consider the impacts of pollution are particularly relevant, such as oil pollution, which can cause considerable damage within mangroves (Duke 2016), and other pollutants, whether from sea or land.…”
Section: Anticipated Impacts On Mangrovesmentioning
confidence: 99%
“…Effective implementation of policies and strategies for littoral zone management requires the application of suitable plans and strict adherence to regulations. A number of scholarly investigations, including those by Camilleri et al (2017), Khamis et al (2017), and Ramesh et al (2017), have underscored the importance of incorporating spatial data concerning ecologically significant regions, coastal habitat conditions, land use, and land cover in order to guarantee the effective implementation of these initiatives.…”
Section: Introductionmentioning
confidence: 99%